Use of transportability methods for real-world evidence generation: a review of current applications - Natalie S Levy; Patrick J Arena; Thomas Jemielita; Shahrul Mt-Isa; Shane McElwee; David Lenis; Ulka B Campbell; Ashley Jaksa; Gleicy M Hair (Becaris Publishing Limited, 2024)
Aim: To evaluate how transportability methods are currently used for real-world evidence (RWE) generation to inform good practices and support adoption and acceptance of these methods in the RWE context. Methods: We conducted a targeted literature review to identify studies that transported an effect estimate of the clinical effectiveness or safety of a biomedical exposure to a target real-world population. Records were identified from PubMed-indexed articles published any time before 25 July 2023 (inclusive). Two reviewers screened abstracts/titles and reviewed the full text of candidate studies to identify the final set of articles. Data on the therapeutic area, exposure(s), outcome(s), original and target populations and details of the transportability analysis (e.g., analytic method used, estimate transported, stated assumptions) were abstracted from each article. Results: Of 458 unique records identified, six were retained in the final review. Articles were published during 2021-2023, focused on the US/Canada context, and covered a range of therapeutic areas. Four studies transported an RCT effect estimate, while two transported effect estimates derived from real-world data. Almost all articles used weighting methods to transport estimates. Two studies discussed all transportability assumptions, and one evaluated the likelihood of meeting all assumptions and the impact of potential violations. Conclusion: The use of transportability methods for RWE generation is an emerging and promising area of research to address evidence gaps in settings with limited data and infrastructure. More transparent and rigorous reporting of methods, assumptions and limitations may increase the use and acceptability of transportability for producing robust evidence on treatment effectiveness and safety.